Playing the Farmer : Representations of Rural Life in Vergil's Georgics - Thibodeau, Philip (Philip J.), 1970- (Book collections on Project MUSE., 2011)
Setting Vergil's Georgics in the social context of its day, the book connects the poem's idyllic, and idealized, portrait of rustic life and agriculture with changing attitudes toward the countryside in late Republican and early Imperial Rome. It argues that what has been seen as a straightforward poem about agriculture is in fact an enchanting work of fantasy that elevated, and sometimes whitewashed, the realities of country life.